Ultrasonic Speeds and Isentropic Compressibility for Binary Mixtures of DMSO with Alkanols - Dewan, R.K.; Mehta, S.K. (Asian Journal of Chemistry, 2010)
Measurement of ultrasonic speed have been carried out on binary mixtures of DMSO with n-alkanol (C6, C7, C8, C10) at 313.15 K over the entire mole fraction range. Ultrasonic velocity values have been used to calculate the values of isentropic compressibility K8, Rao's constant W, intermolecular free length Lf, Van der Waals' constant b, solvation number Sn, and excess free volume VfE. A qualitative discussion of the results is presented.